Measuring the Severity of Topical 5-Fluorouracil Toxicity. Issue 4 (July 2014) - Korgavkar, Kaveri; Firoz, Elnaz F.; Xiong, Michael; Lew, Robert; Marcolivio, Kimberly; Burnside, Nancy; Dyer, Robert; Weinstock, Martin A.
Background: Topical 5% 5-fluorouracil (5-FU) is known to cause toxicity, such as erythema, pain, and crusting/erosions. Objectives: We sought to develop a scale to measure this toxicity and test the scale for reliability. Methods: A scale was developed involving four parameters: erythema severity, percentage of face involved in erythema, crusting/erosions severity, and percentage of face involved in crusting/erosions. Thirteen raters graded 99 sets of photographs from the Veterans Affairs Keratinocyte Carcinoma Chemoprevention (VAKCC) Trial using these parameters. Results: Intraclass correlation overall for 13 raters was 0.82 (95% CI 0.77–0.86). There was no statistically significant trend in reliability by level of training in dermatology. Conclusions: This scale is a reliable method of evaluating the severity of toxicity from topical 5-fluorouracil and can be used by dermatologists and nondermatologists alike.